Genetic variability, character association and path analysis in maize (Zea mays L.) (Bangladesh Journal of Agricultural Research, 2016)
Twenty-two maize hybrids were evaluated to find out their variability, character association and path coefficient of grain yield and its component characters. Significant differences were found among the genotypes for the characters studied. Ear length and grain yield (t/ha) had moderate genotypic coefficient of variation (GCV) and phenotypic coefficient of variation (PCV), but the had the low environmental co-efficient of variation (ECV). The heritability for all the characters was high. The characters viz. plant height, ear height and 1000-grain weight, showed high heritability along with high genetic advance. Ear length, ear diameter and kernel per row had highly significant positive correlation with grain yield. However, the deviations between genotypic and phenotypic correlation and magnitude of environmental correlation suggested considerable influence of growing environment in expressing almost all the characters. Path coefficient analysis revealed that plant height (0.659), ear length (0.934) and kernel-rows per ear (0.715) had highly significant positive direct effect on grain yield suggesting their importance during selection. Simultaneous restricted selection should be done for number of kernel rows per ear.Bangladesh J. Agril. Res. 41(1): 173-182, March 2016